1999
DOI: 10.1523/jneurosci.19-10-j0003.1999
|View full text |Cite
|
Sign up to set email alerts
|

Complex Behavioral Strategy and Reversal Learning in the Water Maze without NMDA Receptor-Dependent Long-Term Potentiation

Abstract: Successful performance of the water maze task requires that rats learn complex behavioral strategies for swimming in a pool of water, searching for and interacting with a hidden platform before its spatial location can be learned. To evaluate whether NMDA receptor-dependent long-term potentiation (NMDA-LTP) is required for learning the required behavioral strategies, rats with NMDA-LTP blocked by systemic pharmacological treatment were trained in the behavioral strategies using simplified and stepwise training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
7
31
0
Order By: Relevance
“…This reduction is comparable to reductions found in previous research using the same equipment, pretraining protocol, and rat strain (Cain, 1997;Cain et al, 1996Cain et al, , 1997Cain et al, , 2000Hoh et al, 1999;Perrot-Sinal et al, 1996;Saucier et al, 1996). As pretraining progressed, rats swam away from the wall and readily used the hidden platform as a refuge.…”
Section: Strategies Pretrainingsupporting
confidence: 78%
See 2 more Smart Citations
“…This reduction is comparable to reductions found in previous research using the same equipment, pretraining protocol, and rat strain (Cain, 1997;Cain et al, 1996Cain et al, , 1997Cain et al, , 2000Hoh et al, 1999;Perrot-Sinal et al, 1996;Saucier et al, 1996). As pretraining progressed, rats swam away from the wall and readily used the hidden platform as a refuge.…”
Section: Strategies Pretrainingsupporting
confidence: 78%
“…Previous work has shown that some drug treatments cause sensorimotor disturbances that could be relevant to performance in the WM task (Beiko et al, 1997;Cain, 1997Cain, , 1998Cain et al, 1996Cain et al, , 1997Cain et al, , 2000Cain et al, , 2002Hoh et al, 1999;Saber and Cain, 2003;Saucier and Cain, 1995;Saucier et al, 1996). Therefore rats were also tested on a beam walking task (Kolb and Whishaw, 1985) that assessed sensorimotor function outside the WM environment under the same drug treatment that was given to the rats before WM training.…”
Section: Experiments 2: Spatial Learning Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter point is important given that the water maze task is highly stressful, as documented by a rapid and large surge in serum corticosterone early in training (Beiko et al, 1997b). The use of pretraining together with a detailed behavioral analysis has shown that strategy impairments and sensorimotor disturbances, but not spatial learning impairments, are the main cause of increased search times in naive animals given SCO (Beiko et al, 1997a;Cain et al, 2000;Saucier et al, 1996), or the benzodiazepine diazepam (Cain, 1997;Cain et al, 2000), or any of a variety of NMDA receptor antagonists (Bannerman et al, 1995;Cain et al, 1996Cain et al, , 1997Cain et al, , 2000Hoh et al, 1999;Saucier and Cain, 1995). In each of the above studies pretrained drugged rats were indistinguishable from controls on behavioral measures of spatial learning.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, with sufficient training, learning in the Morris water maze becomes hippocampus-independent (Hoh et al 1999) and would therefore be assumed to be REM sleep-independent as well. In our hands, animals show robust initial spatial training and initial probe trial performance and were not affected by concurrent REM sleep deprivation in those same initial learning metrics, except under the weakest learning conditions (four trials/day previously maze-exposed animals).…”
Section: Factors Contributing To Lack Of Concurrent Rem Sleep Deprivamentioning
confidence: 99%